2019
DOI: 10.3390/toxins11040198
|View full text |Cite
|
Sign up to set email alerts
|

The Pressure of Fusarium Disease and Its Relation with Mycotoxins in The Wheat Grain and Malt

Abstract: Fusarium head blight (FHB) is one of the most destructive wheat fungal diseases, causing yield loss, quality reduction, and accumulation of mycotoxins. The aim of this research was to summarize the occurrence of major Fusarium mycotoxins: deoxynivalenol (DON), 3-acetyldeoxynivalenol (3-AcDON), nivalenol (NIV), and zearalenone (ZEN) in two consecutive years to search the relationship between disease incidence and severity with mycotoxins found in control and inoculated grains and corresponding malt. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 59 publications
3
19
0
Order By: Relevance
“…Moreover, Lancova et al [28] reported that, during barley grain germination, the concentration of DON may decrease by 90%, while the concentration of DON-3G may markedly increase, to a level as high or several times higher than DON. Spanic et al [30] presented data on mycotoxin levels in wheat varieties varying in Fusarium head blight resistance; the average content of DON-3G increased from 59.9 µg/kg in grain to 163.9 µg/kg in malt.…”
Section: Maltmentioning
confidence: 99%
“…Moreover, Lancova et al [28] reported that, during barley grain germination, the concentration of DON may decrease by 90%, while the concentration of DON-3G may markedly increase, to a level as high or several times higher than DON. Spanic et al [30] presented data on mycotoxin levels in wheat varieties varying in Fusarium head blight resistance; the average content of DON-3G increased from 59.9 µg/kg in grain to 163.9 µg/kg in malt.…”
Section: Maltmentioning
confidence: 99%
“…The use of FHB-resistant wheat cultivars is considered to be the most cost-effective strategy to reduce occurrence and production of mycotoxins in wheat (Buerstmayr et al, 1999;Mesterházy, 1995;Miedaner, 1997). Resistance to FHB is quantitative and can be divided into five types: Type I: resistance to initial infection, type II: resistance to colonisation, type III: limitation of toxin accumulation, type IV: resistance to kernel infection and type V: tolerance to infections (Mesterhazy, 1995;Spanic et al, 2019). Type II resistance has been regarded as the most effective and stably inherited, and its measurement is straightforward with FHB severity scored after point inoculation (Bai and Shaner, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Trichothecenes also function as virulence factors for different Fusarium head blight (FHB) pathogens [39,[180][181][182]. As such, different Fusarium species have been shown to exhibit host preference and different levels of competitiveness in cases of co-infection [183].…”
Section: Factors Affecting the Reliability Of Genotype-chemotype Assomentioning
confidence: 99%